Impact of Financial Literacy, Transaction Interests and Financial Inclusion on Credit Decisions on Peer to Peer (P2P) Lending in the West Medan Sub-District - Sandro Sandro; Muhammad Salman; Mayang Murni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The study aims to find out the impact of financial literacy, transaction interests and financial inclusion on peer to peer lending decisions in the West Medan sub-district. This research data is primary data using a questionnaire as a tool to collect data. Data collection technique with snowball sampling, which is the technique of determining samples that are initially small quantities, then these samples are asked to choose their friends to be used as samples. The population in this study was either online borrowers or those who used peer to peer lending of 202 users in the West Medan sub-district. The statistical analysis used in this study is a multiple linear regression analysis using SPSS (Statistical Package For the Social Science). The results showed that financial literacy has a positive and significant influence on the Peer to Peer Lending Credit Decision. Transaction interests have a negative but significant impact on the peer to peer lending credit decision. Financial inclusion has a significant and positive impact on peer-to-peer lending. The results of the F test have shown that financial Literacy, Transaction Interest and Financial Inclusion have a significant impact upon the Peer to Peer Lending credit Decision simultaneously.